'Vaccine Passports’ may backfire: findings from a cross-sectional study in the UK and Israel on willingness to vaccinate against Covid-19 - Porat,T; Burnell,R; Calvo,R; Ford,E; Paudyal,P; Baxter,W; Parush,A (Vaccines, 2021)
Domestic “vaccine passports” are being implemented across the world, as a way ofincreasing vaccinated people’s freedom of movement and to encourage vaccination. However, thesevaccine passports may affect people’s vaccination decisions in unintended and undesirable ways.This cross-sectional study investigated whether people’s willingness and motivation to getvaccinated relate to their psychological needs (autonomy, competence and relatedness), and howvaccine passports might affect these needs. Across two countries and 1358 participants we foundthat need frustration – particularly autonomy frustration – was associated with lower willingnessto vaccinate and with a shift from self-determined to external motivation. In Israel (a country withvaccine passports), people reported greater autonomy frustration than in the UK (a country withoutvaccine passports). Our findings suggest that control measures, such as domestic vaccine passportsmay have detrimental effects on people’s autonomy, motivation, and willingness to get vaccinated.Policies should strive to achieve a highly vaccinated population by supporting individuals’autonomous motivation to be vaccinated and using messages of autonomy and relatedness, ratherthan applying pressure and external controls.